Eosinophil peroxidase in sputum represents a unique biomarker of airway eosinophilia. Issue 9 (9th August 2013) - Nair, P.; Ochkur, S. I.; Protheroe, C.; Radford, K.; Efthimiadis, A.; Lee, N. A.; Lee, J. J.
Abstract: Background: Sputum eosinophilia has been shown to be a predictor of response to anti‐eosinophil therapies in patients with airway diseases. However, quantitative cell counts and differentials of sputum are labor intensive. The objective of this study was to validate a novel ELISA‐based assay of eosinophil peroxidase (EPX) in sputum as a rapid and reliable marker of airway eosinophils. Methods: The utility of EPX‐based ELISA as an eosinophil‐specific assay was achieved through comparisons with sputum eosinophil differential counts in freshly prepared and archived patient samples from a variety of clinical settings. Results: EPX levels in sputum correlated with eosinophil percentage ( r s  = 0.84) in asthma patients with varying degrees of airway eosinophilia. Significantly, unlike assays of other eosinophil granule proteins (e.g., ECP and EDN), which often detect the presence of these proteins even in asthma patients with neutrophilic bronchitis, EPX‐based ELISA levels are not increased in this subset of asthma patients or in COPD patients lacking evidence of an airway eosinophilia. Moreover, sputum EPX was a surrogate marker of airway eosinophilia in other patient studies (e.g., allergen inhalation and treatment trials the anti‐(IL‐5) therapeutic Mepolizumab™). Finally, EPX levels in cytocentrifuged prepared sputum supernatants correlated with those from rapidly prepared noncentrifuged filtrates of sputum ( r s  = 0.94). Conclusion and clinical implication: EPX‐based ELISA is a valid, reliable, repeatable, and specific surrogate marker of eosinophils and/or eosinophil degranulation in the sputum of respiratory patients. The novel EPX assay is a valid and reproducible eosinophil‐specific assay that can potentially be developed into a point‐of‐care assessment of eosinophil activity in airway secretions.